Antioxidant potential of Pediococcus pentosaceus strains from the sow milk bacterial collection in weaned piglets - Leli Wang; Qihang Liu; Yuwei Chen; Xinlei Zheng; Chuni Wang; Yining Qi; Yachao Dong; Yue Xiao; Cang Chen; Taohong Chen; Qiuyun Huang; Zongzhao Zhai; et al. (Microbiome, 2022)
Abstract Background In modern animal husbandry, breeders pay increasing attention to improving sow nutrition during pregnancy and lactation to favor the health of neonates. Sow milk is a main food source for piglets during their first three weeks of life, which is not only a rich repository of essential nutrients and a broad range of bioactive compounds, but also an indispensable source of commensal bacteria. Maternal milk microorganisms are important sources of commensal bacteria for the neonatal gut. Bacteria from maternal milk may confer a health benefit on the host. Methods Sow milk bacteria were isolated using culturomics followed by identification using 16S rRNA gene sequencing. To screen isolates for potential probiotic activity, the functional evaluation was conducted to assess their antagonistic activity against pathogens in vitro and evaluate their resistance against oxidative stress in damaged Drosophila induced by paraquat. In a piglet feeding trial, a total of 54 newborn suckling piglets were chosen from nine sows and randomly assigned to three treatments with different concentrations of a candidate strain. Multiple approaches were carried out to verify its antioxidant function including western blotting, enzyme activity analysis, metabolomics and 16S rRNA gene amplicon sequencing. Results The 1240 isolates were screened out from the sow milk microbiota and grouped into 271 bacterial taxa based on a nonredundant set of 16S rRNA gene sequencing. Among 80 Pediococcus isolates, a new Pediococcus pentosaceus strain (SMM914) showed the best performance in inhibition ability against swine pathogens and in a Drosophila model challenged by paraquat. Pretreatment of piglets with SMM914 induced the Nrf2-Keap1 antioxidant signaling pathway and greatly affected the pathways of amino acid metabolism and lipid metabolism in plasma. In the colon, the relative abundance of Lactobacillus was significantly increased in the high dose SMM914 group compared with the control group. Conclusion P. pentosaceus SMM914 is a promising probiotic conferring antioxidant capacity by activating the Nrf2-Keap1 antioxidant signaling pathway in piglets. Our study provided useful resources for better understanding the relationships between the maternal microbiota and offspring. Video Abstract